936. Body Fat Redistribution/Accumulation, Pancreatic Disorders, Musculoskeletal Disorders, IRIS, Severe Systemic Rash and Hypersensitivity Reactions Following Initiation of Commonly Prescribed Antiretrovirals. (26th November 2018) - Lackey, Philip; Brunet, Laurence; Fusco, Jennifer; Vannappagari, Vani; Ragone, Leigh; Fusco, Gregory
Abstract: Background: Dolutegravir (DTG), elvitegravir (EVG), raltegravir (RAL), and darunavir (DRV) are commonly used for the treatment of HIV. We assessed the frequency of 6 select disorders after prescription of DTG-, EVG-, RAL-, or DRV-based regimens. Methods: HIV-positive patients in the OPERA® Observational Database initiating DTG-, EVG-, RAL-, or DRV-containing regimens were included. Disorders of interest were body fat redistribution/accumulation, pancreatic disorders, and musculoskeletal disorders, as defined in Figures 2–3, as well as immune reconstitution inflammatory syndrome (IRIS), severe systemic rash and hypersensitivity reaction (HSR). Baseline patient characteristics and disorder history were described. The proportion of patients with disorders of interest during follow-up were compared between core agents for each disorder. All events occurring during follow-up were considered prevalent, while incident disorders excluded patients with any history of disorder. To account for multiple comparisons, the Sidak Correction was applied (adjusted α level: 0.017). Results: Out of 22, 674 patients, 7, 860 (35%) initiated DTG, 9, 738 (43%) EVG, 1, 600 (7%) RAL, and 3, 477 (15%) DRV. Baseline demographic and clinical characteristics varied by core agent initiated (Figure 1). Compared with DTG, history of body fat redistribution/accumulation was less frequent in patients initiating EVG, and more frequent in patients initiating RAL (Figure 2). EVG users also had a lower prevalence during follow-up than DTG users (Figure 3). However, there was no difference in new onset of body fat redistribution/accumulation between groups (Figure 3). No difference in prevalent or incident pancreatic or musculoskeletal disorders was detected between core agents (Figure 3). IRIS, severe systemic rash, and HSR occurred in no more than 2 patients per core agent group, with no difference detected between groups. Conclusion: Incident body fat redistribution/accumulation, pancreatic disorders, musculoskeletal disorders, IRIS, severe systemic rash, and HSR were rare in this large cohort of patients initiating DTG, EVG, RAL, or DRV. Despite some channeling of patients with a disorder history towards DTG and RAL use, the likelihood of new events did not differ by core agent. Disclosures: L. Brunet, Epividian, Inc.: Employee, Salary. ViiV Healthcare: ViiV Healthcare has contracted research with my employer, Epividian, Inc., Employer received funding for research. Merck: Merck has contracted research with my employer, Epividian, Inc., Employer received funding for other research. J. Fusco, Epividian, Inc.: Employee, Salary. ViiV Healthcare: Viiv Healthcare contracted research with my employer, Epividian, Inc., Employer received funding for research. Merck & Co.: Merck contracted research with my employer, Epividian, Inc., Employer received funding for research. V. Vannappagari, ViiV HealthCare: Employee, GlaxoSmithKline Company Stock and Salary. L. Ragone, ViiV Healthcare: Employee and Shareholder, restricted shares and Salary. G. Fusco, Epividian, Inc.: Employee, Salary. ViiV Healthcare: Viiv Healthcare contracted research with my employer, Epividian, Inc., Employer received funding for research. Merck & Co.: Merck contracted research with my employer, Epividian, Inc., Employer received funding for research.